Evaluation of new rotor angle deviation regulator for synchronous generator using nonlinear swing equation - Mohamad Murad, Nor Syaza Farhana (2024)
In power system operation, a deviation of the rotor angle of a synchronous generator perturbs the oscillation, deteriorates system performance, and damages protection schemes. In the case of an interconnected power system, any disturbances that occur cause a discrepancy in the rotor angle. Previous studies on rotor angle stability enhancement only focus on the simplified model that adopts a linearized swing equation where the damping power has been neglected, making the accuracy of the model disputed. As such, the need to develop a control algorithm for a synchronous generator of power system is crucial. In order to obtain stabilization upon rotor angle deviation, a regulator based on the Lypapunov algorithm for a synchronous generator is proposed in this research. The dynamic model of a synchronous generator is developed through the swing equation. Nonlinear parameters are included in the modeling, and hence the synchronous generator is portrayed as a nonlinear swing equation. From the nonlinear swing equation, the crucial parameters that affect the stability and transient performance of the synchronous generator are the synchronizing coefficient,